The impact of COVID-19 lockdown on snacking habits, fast-food and alcohol consumption: A systematic review of the evidence - Bakaloudi, Dimitra Rafailia (Clin Nutr, 2022)
The pandemic of coronavirus disease 2019 (COVID-19) and lockdown measures, that were implemented in many countries in order to control the virus transmission, had negatively influenced the lifestyle of millions of people worldwide. In this study we aimed to investigate the impact of the first COVID-19 lockdown period (March–May 2020) on snacking behavior, fast-food and alcohol consumption. A systematic search in PubMed®, Scopus® and Web of Science® databases was conducted and 32 studies were included. Changes in snacking, in fast-food and ordered food consumption and in alcohol intake were examined. Snacking was found to be increased for a significant portion of the population examined (18.9–45.1%), whereas fast food (15.0–41.3%) and ordered food (33.9%) showed a tendency towards decrease. As per alcohol consumption, an upward trend was observed in a significant part (10.4–51.0%) of the participants examined. The increased snacking and alcohol consumption observed for almost a third of the examined population could be alarming because long-term health problems could arise in cases of repeated lockdowns in the future. The observed downward trend in fast-food consumption and in frequency of ordered food could be an encouraging sign of turning to home-prepared foods, but further research is needed in this field.